ANALISA KINERJA TEKNOLOGI ANTENA MIKROSTRIP RECTANGULAR PATCH MENGGUNAKAN COMPUTER SIMULATION TECHNOLOGY DAN ADVANCED DESIGN SYSTEM PADA FREKUENSI 2,4 GHZ - Yuyun Suprapto; Denny Andareas Siringoringo; Meita Maharani Sukma (Politeknik Penerbangan Surabaya, 2019)
Microstrip antenna is an antenna that is widely developed in various applications. Microstrip antennas are very attractive because of their light weight, easy adjustment of shape and low cost. In radio wave communication, an antenna that has good performance is needed: bandwidth, working frequency, VSWR, and good gain. This study aims to design a rectangular patch microstrip antenna with existing antenna parameters, so that it can be used as a learning medium in the air navigation engineering study program. The author conducted an experiment by designing and analyzing the performance of a microstrip antenna with a rectangular patch shape at a frequency of 2.4 GHz using the CST Studio Suite 2018 software and the ADS 2019 software as a simulator. The use of Epoxy FR-4 as a substrate is based on the aim of designing a smaller antenna but it has an impact on lower antenna efficiency and a wide antenna bandwidth. This is because the relative permittivity values and the dielectric thickness are quite large, namely 4.8 and 1.6 mm. The antenna specifications to be designed are obtained from calculations, namely the patch width is 36.70 mm, the patch length is 29.03 mm. The results of simulation work using CST Studio Suite 2018 software and ADS 2019 software show the optimal working frequency at 2,388GHz. Parameters such as return loss, bandwidth, VSWR, and gain in the two simulators are different, the CST Studio Suite 2018 application design is more in line with the expected Long Term Evolution (LTE) antenna specifications.